2016
DOI: 10.1177/0333102416640501
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic mechanisms in the migraine brain – a systematic review

Abstract: Background Migraine is one of the most common and disabling of all medical conditions, affecting 16% of the general population, causing huge socioeconomic costs globally. Current available treatment options are inadequate. Serotonin is a key molecule in the neurobiology of migraine, but the exact role of brain serotonergic mechanisms remains a matter of controversy. Methods We systematically searched PubMed for studies investigating the serotonergic system in the migraine brain by either molecular neuroimaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
55
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 83 publications
(58 citation statements)
references
References 88 publications
2
55
0
1
Order By: Relevance
“…Although an unaltered 5‐HT blood level is observed in some strata, altered 5‐HT levels might exist in the brain 62 . 5‐HT in blood is mainly located in platelets but upon release, 5‐HT is rapidly broken down to 5‐hydroxyindoleacetic acid (5‐HIAA) which is often used as a surrogate measure.…”
Section: Discussionmentioning
confidence: 99%
“…Although an unaltered 5‐HT blood level is observed in some strata, altered 5‐HT levels might exist in the brain 62 . 5‐HT in blood is mainly located in platelets but upon release, 5‐HT is rapidly broken down to 5‐hydroxyindoleacetic acid (5‐HIAA) which is often used as a surrogate measure.…”
Section: Discussionmentioning
confidence: 99%
“…Hypersensitization of the brainstem trigeminal sensory complex may underlie the primary brain dysfunction in migraine [1; 10; 58; 71], leading to brainstem-mediated upregulation of cortical excitability [14; 40]. Therapeutic options have targeted brainstem neuromodulatory centers, including serotonergic (raphe nuclei) and noradrenergic (locus coeruleus) nuclei [19; 63], via dihydroergotamine, triptans, and other 5HT1B/1D agonists [21; 41; 62]. More recently, novel neuromodulation therapies have been proposed [44; 65].…”
Section: Introductionmentioning
confidence: 99%
“…The migraine group had worse findings for all parameters, suggesting that autonomic dysfunction is either a risk factor for migraine headaches or a consequence of frequent disabling attacks. Furthermore, migraine‐related alterations in cerebral serotonergic neurotransmission were reported by Deen et al, who found that in patients with migraine, cerebral 5‐HT3 level is low between attacks and rises during attacks. The role of SP in migraine was illustrated in a series of innovative experimental migraine models.…”
Section: Discussionmentioning
confidence: 83%